Humic extracts from hydrochar and Amazonian Anthrosol: Molecular features and metal binding properties using EEM-PARAFAC and 2D FTIR correlation analyses - Soares da Silva, Leila [UNESP]; Constantino, Isabela Carreira [UNESP]; Bento, Lucas Raimundo [UNESP]; Tadini, Amanda Maria; Bisinoti, Márcia Cristina [UNESP]; Boscolo, Maurício [UNESP]; Ferreira, Odair Pastor; Mounier, Stéphane; Piccolo, Alessandro; Spaccini, Riccardo; Cornélio, Marinônio Lopes [UNESP]; Moreira, Altair Benedito [UNESP] (Elsevier, 2020)
Organic matter plays many roles in the soil ecosystem. One property of the substance concerns the metal complexation and interaction with organic contaminants. In this sense, the humic substances (HS), a heterogeneous mixture of compounds, naturally derived from degradation of biomass, have been widely studied in environmental sciences. Recent advances showed a new way to produce humic-like substances (HLS) through hydrothermal carbonization of biomass. Thus, this study aimed to evaluate the HLS of hydrochars, produced by using a mixture of sugarcane bagasse and vinasse with sulfuric acid added (1 and 4% v/v), and to assess their interactions with metal ions, (Fe(III), Al(III), Cu(II) and Co(II)) using EEM-PARAFAC and a two-dimensional FTIR correlation analysis. The results were compared to the humic substances extracted from the Amazonian Anthrosol, as a model of anthropogenic organic matter. NMR analysis showed that humic-like extracts from hydrochar are mainly hydrophobic, while the soil has a greater contribution of polar moieties. The HLS and HS showed similar complexation capacities for Fe(III), Al(III) and Cu(II) assays. For Co(II) HLS exhibited larger affinities than HS. Two-dimensional correlation analysis FTIR showed that chemical groups may undergo conformational alteration with metal additions to achieve more stable arrangements (higher stability constant). Therefore, these results contribute more knowledge about the mechanism of HS and metal ion interaction, as well as showing that HTC can be an interesting option for HLS production, to be used as humic based materials.
Keywords: 13C-CPMAS-NMR; Complexation; Humic-like substances; Hydrothermal carbonization; Nutrients; Soil organic matter